1853 Terr. of N.M. Laws 406 - (:unkn) unknown (My University, 1853)
An Act Prohibiting the Carrying of Weapons Concealed or Otherwise, § 25: Prohibited the carrying of a concealed pistol, Bowie knife (cuchillo de cinto), Arkansas toothpick, Spanish dagger, slungshot, or any other deadly weapon.
Keywords: CARRY - CONCEALED